Effect of steam sterilisation on lipophilic nutrient stability in a chloroplast-rich fraction (CRF) recovered from postharvest, pea vine field residue (haulm). (1st January 2021) - Wattanakul, Jutarat; Syamila, Mansor; Briars, Rhianna; Ayed, Charfedinne; Price, Ruth; Darwish, Randa; Gedi, Mohamed A.; Gray, David A.
Highlights: Pea vine haulm can be physically processed to a green powder rich in chloroplasts. Heat treatment of this pea vine haulm helps to stabilise nutrients. Carotenoid and vitamin E in the material were stable under the storage condition. The stability of carotenoid and vitamin E was reduced at higher temperatures. Abstract: Postharvest, pea vine field residue (haulm) was steam-sterilised and then juiced; a chloroplast-rich fraction (CRF) was recovered from the juice by centrifugation. The stability of selected nutrients (β-carotene, lutein, and α-tocopherol) in the freeze-dried CRF material was measured over 84 days; the impact of temperature (-20 °C, 4 °C, 25 °C and 40 °C), light and air on nutrient stability was established. All three nutrients were stable at −20 °C and 4 °C in the presence or absence of air; this stability was lost at higher temperatures in the presence of air. The extent and rate of nutrient breakdown significantly increased when the CRF samples were exposed to light. β-Carotene appeared to be more susceptible to degradation than lutein and α-tocopherol at 40 °C in the presence of air, but when CRF was exposed to light all three nutrients measured were significantly broken down during storage at 25 °C or 40 °C, whether exposed to air or not.